ANALISIS SINTAKSIS TERHADAP KEEFEKTIPAN KALIMAT DALAM TEKS BERITA DARING ANTARANEWS.COM EDISI MARET 2025 - Trisnawati; Andoyo Sastromiharjo; Rika Kustina; Barkatun Nisa Alfia; Arianto; Stella Talitha; Muhammad Bujaya; Nina (Program Studi Pendidikan Bahasa dan Sastra Indonesia, FKIP, Universitas Halu Oleo Kampus Bumi Tridharma Andounohu Kendari, Provinsi Sulawesi Tenggara – Indonesia, 2025)
This study examines the effectiveness of sentences in online news texts published by Antaranews.com in the March 2025 edition through a syntactic analysis approach. The main focus of the study is to analyze how the syntactic structure of sentences affects the clarity and accuracy of information delivery in news texts. The background of this study is based on the widespread use of long and complicated sentences in online news that can hinder readers' understanding. The purpose of this study is to find ineffective sentence forms and to formulate the characteristics of syntactic structures that are able to convey information clearly and communicatively. The method used is qualitative descriptive with content analysis techniques on 20 news texts from various fields, namely politics, economics, social, and culture. The results of the analysis show that although most sentences use complex compound structures, not all of them are able to convey messages effectively. Some of the problems found include inconsistencies in the relationship between parts of the sentence, structural ambiguity, and excessive use of elements. These findings indicate the importance of constructing sentences that are denser, more straightforward, and easier to understand in writing online news.